2014
DOI: 10.3109/1547691x.2014.960108
|View full text |Cite
|
Sign up to set email alerts
|

DDE and PCB 153 independently induce aryl hydrocarbon receptor (AhR) expression in peripheral blood mononuclear cells

Abstract: Recent studies have demonstrated that compounds inducing pro-inflammatory cytokines enhance AhR expression. The aim of this study was 2-fold: (1) to determine if two pro-inflammatory compounds, dichlorodiphenyldichloroethylene (DDE) and 2,2 0 ,4,4 0 ,5,5 0 -hexa-chlorobiphenyl (PCB 153), independently affect AhR gene expression in peripheral blood mononuclear cells (PBMC); and (2) if affected, to determine whether the mechanism involved was due to AhR activation or to a pro-inflammatory effect of the chemicals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In addition, AhR and non-AhR effects are difficult to separate on gene-level. One study found that DDE and PCB 153 up-regulated expression of AhR mRNA independent of direct AhR activation [45]. It was suggested that the induction of AhR expression was induced by NF-κB which promotes an inflammatory loop, via pro-inflammatory cytokines expression as interleukin (IL)-1 β and TNFα [46].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AhR and non-AhR effects are difficult to separate on gene-level. One study found that DDE and PCB 153 up-regulated expression of AhR mRNA independent of direct AhR activation [45]. It was suggested that the induction of AhR expression was induced by NF-κB which promotes an inflammatory loop, via pro-inflammatory cytokines expression as interleukin (IL)-1 β and TNFα [46].…”
Section: Discussionmentioning
confidence: 99%
“…Gene transcription of aryl hydrocarbon receptor nuclear translocator (ARNT) and aryl hydrocarbon receptor (AHR) and peroxisome proliferator-activated receptor alpha (PPARα) showed significant relationships with HCB, chlordanes, DDTs, 29 PCBs, and PCB homologs groups, but not with PBDEs and 3-Cl biphenyls. AHR and ARNT are induced by environmental contaminants and mediate immunotoxic compounds (Gaspar-Ramírez et al, 2015). AHR, ARNT and PPARα transcription were previously found to be associated with the exposure to organic pollutants in Baikal seals (Kim et al, 2005;Ishibashi et al, 2008) and in harbor seals (Lehnert et al, 2016).…”
Section: Gene Transcripts and Persistent Organic Pollutantsmentioning
confidence: 95%